2018
DOI: 10.1097/sap.0000000000001613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Posthospital Syndrome on Health Care Utilization After Abdominal Contouring Surgery

Abstract: Background: Post-hospital syndrome (PHS) is a transient condition after acute hospitalizations when patients are physiologically deconditioned. The objective of this study was to determine if having PHS at the time of abdominal contouring surgery increased the incidence of post-operative adverse medical events. Methods: We conducted a retrospective cohort study of patients enrolled in the MarketScan Databases who underwent outpatient functional or cosmetic abdominal contouring surgery (i.e. abdominoplasty, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This is attributed to many factors related to surgery, including pain, acute blood loss anemia, and the inflammatory phase of healing. Furthermore, it is well established that patients experience physical deconditioning from the impact of being hospitalized 18,19 . This is related to several factors including poly-pharmacy (notably narcotics), disturbance in sleep-wake cycle, malnutrition, and the psychosocial stress of being hospitalized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is attributed to many factors related to surgery, including pain, acute blood loss anemia, and the inflammatory phase of healing. Furthermore, it is well established that patients experience physical deconditioning from the impact of being hospitalized 18,19 . This is related to several factors including poly-pharmacy (notably narcotics), disturbance in sleep-wake cycle, malnutrition, and the psychosocial stress of being hospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is well established that patients experience physical deconditioning from the impact of being hospitalized. 18,19 This is related to several factors including poly-pharmacy (notably narcotics), disturbance in sleep-wake cycle, malnutrition, and the psychosocial stress of being hospitalized. Studies have found that patients are transiently vulnerable in the posthospitalization period and are at an increased risk of complications and increased health care utilization (eg, emergency department visits).…”
Section: Discussionmentioning
confidence: 99%